Nonlinear Elastoplastic Response and Damage Modeling in Power Electronics Packages Under Thermal Cycling - Giuseppe Mirone; Raffaele Barbagallo; Luca Corallo; Giuseppe Bua; Guido La Rosa; Giovanna Fargione; Fabio Giudice (Engineering Proceedings)
One of the common reliability tests performed on power modules for automotive applications is passive thermal cycling, which is conventionally representative of the highly demanding thermomechanical loads typical of steady-state operating conditions. The mechanical response of the electronics devices subjected to such testing procedures, in terms of stress-strain response and of damage, is usually predicted by finite elements analyses where the remarkable nonlinearities intrinsic in the phenomena need to be properly addressed. This work regards the FEM modeling of the thermomechanical behavior of a power electronics package subjected to thermal cycles, focusing on the critical importance of modeling the complete elastoplastic behavior of materials, in contrast to the conventional elastic approach. By incorporating the full elastoplastic properties, the study aims to accurately evaluate the actual irreversible deformations and resulting stresses that develop within the package subjected to a representative passive thermal cycle and to compare the outcomes to those from purely elastic simulations. Additionally, damage models are compared for predicting the local detachment of the encapsulating resin from other layers. The predictions of the cohesive zone model (CZM) applied to a conventional interface layer are compared to those of a modified Tresca (MT) stress-dependent damage model applied to the resin bulk material. In addition, the estimate of linear-nonlinear evolutions of plastic strain and of damage at increasing numbers of cycles is investigated in the attempt to identify procedures for guessing the long-term mechanical response from short-term simulations.